Peatlands Restoration Policies in Indonesia: Success or Failure?. Issue 1 (1st April 2022) - Wicaksono, Agung; Zainal,
Abstract: This paper describes and analyzes the peatland restoration policy undertaken by the Indonesian government. The Indonesian government has since implemented the first phase of peatland restoration in 2016-2020. It can be said that the restoration of the peatland area of 2.4 million hectares faces several problems. One of the main problems is the unsuccessful restoration of peatlands in the company's concession areas. Companies that are obliged to restore peatlands in their concessions do not comply with regulations set by the government. As the program's leader, the Peatland Restoration Agency is powerless to do much because its authority extends only to supervising the company's concession area. Restoration of peatlands outside the concession area (cultivated land and protected forest) can be satisfied because the government can directly restore these peatlands. This paper uses various reliable document sources as the primary data source, which becomes material for analysis.